Preclinical Medical Students' Awareness About Disabled Friendly Campus - KARAVUŞ, MELDA; DAVUN, SELİN; HIDIROĞLU, SEYHAN (MARMARA UNIV, INST HEALTH SCIENCES, 2021)
Objective: The Disabled Friendly Campus is relatively new consept in the world. In this study we aimed to evaluate the awareness of preclinical medical students about the Disabled Friendly Campus. Methods: Cross-sectional study was conducted at a public university's Faculty of Medicine Campus. In our study, 362 students were included and the data were obtained between March and June 2019. A questionnaire was prepared in the light of the literature. In the first part of the questionnaire, socio-demographic features were questioned; In the second part of the questionnaire there were 13 questions about the arrangements required for a disabled person on a campus. Answer options such as 1= I don't agree, 2= I have no idea and 3= I agree. The score varied between 13-39, and as the total score obtained increases, it was assumed that the awareness of Disabled Friendly Campus will increase. Results: In our study 3.3% (n = 12) of the participants had any disability, and 18.2% (n = 66) had a disabled person in their family. A statistically significant difference was observed between the participants' disabled friendly campus awareness scores according to their gender, class, their participation in an activity related to disabled people and whether they found their campuses suitable for disabled people. Conclusion: It can be suggested that the questionnaire, which is assumed to evaluate the awareness of preclinical medical students on Disabled Friendly Campus, can be made into a scale with high validity and reliability.
Keywords: Students; Medical Faculty; Disabilities; DISABILITY; ATTITUDES; PEOPLE